Anti-corrosion coating and preparation method thereof, battery pack and electric equipment
By introducing magnetic water-absorbing resin and hydrophobic nano SiO2 coating into the anticorrosion coating, the problem of coating failure caused by moisture penetration is solved, and the long-term anti-corrosion effect of the coating is achieved.
Patent Information
- Application Number
- CN202411445839.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-04-08
AI Technical Summary
Existing anticorrosion coatings are prone to failure due to moisture infiltration during long-term use, resulting in failure of coating adhesion and accelerated corrosion.
An anticorrosion coating layer including a second epoxy resin layer, a transition layer, a first epoxy resin layer and a hydrophobic layer is adopted. A magnetic water-absorbing resin and an epoxy resin are used in the transition layer. The hydrophobic layer is a hydrophobic nano SiO2 coating. Through the water absorption and water release reaction of the magnetic water-absorbing resin, water molecules are prevented from infiltration and extended the anticorrosion time of the coating.
Effectively prevent water molecules from infiltration and combining with the matrix interface, extend the anti-corrosion time of the coating, and avoid coating shedding and corrosion acceleration.
Smart Images

Figure CN119775852A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to an anti-corrosion coating and a preparation method thereof, a battery pack and electrical equipment. Background Art
[0002] In order to avoid economic losses caused by metal corrosion, anti-corrosion coatings are widely used on the surface of metal substrates as one of the most effective corrosion prevention methods.
[0003] The main function of anti-corrosion coating is physical barrier, that is, the metal substrate is separated from the external environment by the coating, thereby avoiding the interaction between the metal and the corrosive medium in the surrounding environment. However, due to the presence of defects such as microcracks and pores in the coating itself, the use of coating for corrosion protection still faces the problem that the metal may be exposed to the corrosive environment, which accelerates the corrosion at the damaged part of the coating.
[0004] In order to solve the above difficulties, a new anti-corrosion strategy of using super-hydrophobic materials to prepare anti-corrosion coatings has emerged in recent years. However, during the long-term use of super-hydrophobic anti-corrosion coatings, trace amounts of water molecules may still penetrate into the coating. Once water molecules penetrate, the hydrophobic ability of the coating decreases, and the water molecules quickly gather at the interface between the coating and the substrate, causing the coating to fail in adhesion. Summary of the invention
[0005] The present invention provides an anti-corrosion coating, which has both water absorption and hydrophobic capabilities, and can effectively prevent water molecules from penetrating into and combining with a substrate interface, thereby extending the anti-corrosion time of the coating and avoiding the problem of coating shedding.
[0006] The present invention also provides a method for preparing the anti-corrosion coating. The method can obtain the anti-corrosion coating and is simple to operate.
[0007] The present invention also provides a battery pack including the above-mentioned anti-corrosion coating, which can effectively prevent water molecules from entering the interior of the battery pack, thereby avoiding electrolyte leakage and ensuring the safe operation of the battery.
[0008] The present invention further provides an electrical device. Since the electrical device includes the battery pack, the service life of the electrical device is relatively long.
[0009] In detail, in the first aspect, the present invention provides an anti-corrosion coating, which is arranged on the surface of a substrate. The anti-corrosion coating includes, from the surface adjacent to the substrate to the surface far from the substrate, the following layers are stacked in sequence: a second epoxy resin layer, a transition layer, a first epoxy resin layer and a hydrophobic layer, and the transition layer includes: a magnetic absorbent resin and an epoxy resin.
[0010] Furthermore, the magnetic water-absorbing resin comprises a water-absorbing high molecular polymer and Fe3O4; and / or the contact angle of the hydrophobic layer is greater than 90°.
[0011] Furthermore, the water-absorbing high molecular polymer includes at least one of polyacrylic acid, polyacrylic acid salt, polyacrylamide, and carboxymethyl cellulose; and / or the hydrophobic layer is a hydrophobic nano-SiO2 coating.
[0012] Furthermore, the particle size of the Fe3O4 is 10-50nm.
[0013] Further, the thickness of the first epoxy resin layer is 20-50 μm; and / or the thickness of the second epoxy resin layer is 70-100 μm.
[0014] Further, the thickness of the hydrophobic layer is 20-50 μm; and / or the thickness of the transition layer is 40-60 μm.
[0015] Furthermore, the mass ratio of the magnetic water-absorbing resin to the epoxy resin is 1-3:10-30.
[0016] Furthermore, the transition layer is prepared by a method comprising the following process:
[0017] A first slurry including magnetic water-absorbing resin particles, epoxy resin, curing agent and solvent is applied to at least one surface of the substrate, and a magnet that repels the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles toward the substrate. After the coating is dry, a magnet that attracts the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles away from the substrate. After heating and curing, the transition layer is obtained.
[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned anti-corrosion coating, comprising the following steps:
[0019] 1) A first slurry including magnetic water-absorbing resin particles, epoxy resin, curing agent and solvent is applied to at least one surface of the substrate, a magnet that repels the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles toward the substrate, and after the coating is dried, the first epoxy resin layer is formed, and then a magnet that attracts the nanoparticles of the magnetic water-absorbing resin is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles away from the substrate. After curing, a second epoxy resin layer, a transition layer and a first epoxy resin layer are sequentially stacked on the surface of the substrate;
[0020] 2) spraying a second slurry containing hydrophobic nano-SiO2 on the surface of the first epoxy resin layer, and obtaining the anti-corrosion coating after drying.
[0021] Furthermore, the magnetic water-absorbing resin microparticles are prepared by a method comprising the following steps:
[0022] Polyacetamide, ferrous chloride tetrahydrate, ammonia water, acrylic acid, initiator, crosslinking agent, dispersant and solvent are mixed, and after polymerization reaction, the mixture is dried and crushed to obtain microparticles of the magnetic water-absorbing resin.
[0023] In a third aspect, the present invention provides a battery pack comprising the anti-corrosion coating described in the first aspect.
[0024] In a fourth aspect, the present invention provides an electrical device comprising the battery pack described in the second aspect.
[0025] The anti-corrosion coating provided by the present invention has both water absorption and hydrophobic capabilities, which can effectively prevent water molecules from penetrating and combining with the substrate interface, thereby extending the anti-corrosion time of the coating. In detail: the hydrophobic layer can isolate most of the water molecules, but in special environments, trace water molecules will still penetrate into the hydrophobic layer. The water molecules that penetrate from the hydrophobic layer are quickly absorbed by the transition layer of the anti-corrosion coating, thereby blocking the continued penetration of water molecules and preventing the water molecules from combining with the substrate interface. When the substrate is in a dry state again, the water molecules that have originally penetrated can also evaporate along the previous penetration path. At this time, the transition layer restores its original water absorption capacity, thereby significantly extending the anti-corrosion time of the anti-corrosion coating and preventing the coating from falling off. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 An anti-corrosion coating according to a specific embodiment of the present invention;
[0028] In the figure, 1-substrate; 2-second epoxy resin layer; 3-transition layer; 4-first epoxy resin layer; 5-hydrophobic layer; 6-magnetic water-absorbing resin;
[0029] Figure 2 The anti-corrosion principle of the anti-corrosion coating of a specific embodiment of the present invention;
[0030] In the figure, 1-substrate; 2-second epoxy resin layer; 3-transition layer; 4-first epoxy resin layer; 5-hydrophobic layer; 6-magnetic water-absorbing resin. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In a first aspect, the present invention provides an anti-corrosion coating, Figure 2 The anti-corrosion coating is arranged on the surface of the substrate 1. The anti-corrosion coating includes: a second epoxy resin layer 2, a transition layer 3, a first epoxy resin layer 4 and a hydrophobic layer 5 stacked in sequence from the surface adjacent to the substrate to the surface away from the substrate. The transition layer includes: a magnetic water-absorbing resin and an epoxy resin.
[0033] Among them, the hydrophobic layer can prevent most of the water from entering the anti-corrosion coating. However, in special environments, for example, some parts of the battery pack will store water. In this case, trace amounts of water molecules will penetrate into the hydrophobic layer. Due to the pores in the epoxy resin structure itself, it is difficult to prevent the penetration of water molecules with smaller particle sizes. Especially when the coating is deformed or the operating temperature changes, water molecules are more likely to penetrate into the epoxy resin, causing the adhesion between the substrate and the epoxy resin layer at the interface to fail, and the coating begins to blister. The present invention arranges a magnetic water-absorbing resin in the transition layer. When water molecules penetrate into the transition layer along the gaps in the epoxy resin, the magnetic water-absorbing resin will quickly absorb the water molecules and a water absorption reaction will occur (see Figure 2 ), which can block the continued infiltration of trace water molecules, thereby ensuring that the water molecules are isolated from contact with the substrate; when the substrate is in a dry state again, the magnetic water-absorbing resin will release water after absorbing water, causing the water molecules to evaporate again along the previous path. At this time, the transition layer restores its original water absorption capacity, so that the anti-corrosion coating can achieve long-term corrosion protection. In addition, the main components of the first epoxy resin layer and the second epoxy resin layer are epoxy resin, and epoxy resin is denser than the transition layer. Therefore, an epoxy resin layer is provided between the hydrophobic layer and the transition layer and between the transition layer and the substrate, which can add a layer of water-proof protection, that is, prevent or slow down the infiltration of water, and prevent the transition layer from accelerating the infiltration of water molecules due to the water absorption reaction. At the same time, the epoxy resin layer has stronger adhesion than the transition layer. Therefore, the provision of the epoxy resin layer can also enhance the bonding between the hydrophobic layer, the transition layer, the substrate, etc., and improve the reliability of the anti-corrosion coating.
[0034] In some embodiments, the water absorption reaction is a hydration reaction between the hydrophilic groups in the epoxy resin and the water molecules, for example, -COOH, -CONH2, -OH, etc. are combined with the water molecules through chemical bonding; the water release reaction refers to the epoxy resin being affected by the external osmotic pressure or humidity gradient after absorbing water, and the bonds formed by the hydrophilic groups after absorbing water will break, resulting in water release.
[0035] In a specific embodiment, the magnetic water-absorbing resin comprises a water-absorbing high molecular polymer and Fe3O4; and / or the contact angle of the hydrophobic layer is greater than 90°.
[0036] It can be understood that in the above embodiment, Fe3O4 provides magnetism and the water-absorbing polymer provides water absorption. Exemplarily, the contact angle of the hydrophobic layer is 95°, 100°, 105°, 110°, 115°, 120°, 125°, 130°, etc. or a range consisting of any two of them.
[0037] In some embodiments, the transition layer may further include auxiliary additives such as a tackifier, a thickener, and a surfactant.
[0038] In a specific embodiment, the water-absorbing high molecular polymer includes at least one of polyacrylic acid, polyacrylic acid salt, polyacrylamide, and carboxymethyl cellulose; and / or the hydrophobic layer is a hydrophobic nano-SiO2 coating.
[0039] Among them, the water-absorbing high molecular polymer of the above embodiment has good water absorption and can absorb water hundreds of times heavier than its own weight, which can achieve a better effect of blocking the penetration of trace water molecules, and help to further extend the anti-corrosion time of the anti-corrosion coating.
[0040] The main component of the hydrophobic nano-SiO2 coating is silicon dioxide (SiO2) nanoparticles. In order to achieve better hydrophobicity, in some embodiments, hydrophobic groups (such as methyl, fluoroalkyl, etc.) exist on the surface of the silicon dioxide nanoparticles.
[0041] In a specific embodiment, the particle size of the Fe3O4 is 10-50 nm. The particle size of Fe3O4 is in the range of 10-50 nm, which can further ensure the uniformity of the transition layer and the bonding strength between the first epoxy resin layer and the first epoxy resin layer.
[0042] In a specific embodiment, the thickness of the first epoxy resin layer is 20-50 μm; and / or the thickness of the second epoxy resin layer is 70-100 μm.
[0043] Among them, the thickness of the first epoxy resin layer is between 20-50μm, which can better prevent or slow down the penetration of moisture, and at the same time does not affect the water absorption effect of the transition layer; the thickness of the second epoxy resin layer is between 70-100μm, which can prevent moisture from contacting the substrate and avoid defects such as increased cost, reduced flexibility and adhesion caused by excessive thickness of the anti-corrosion coating.
[0044] Exemplarily, the thickness of the first epoxy resin layer is 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, etc., and the thickness of the second epoxy resin layer is 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, etc.
[0045] In a specific embodiment, the thickness of the hydrophobic layer is 20-50 μm; and / or the thickness of the transition layer is 40-60 μm.
[0046] Among them, the thickness of the hydrophobic layer is between 20-50μm, which can fully exert its hydrophobic effect and avoid the problems of increased cost of the anti-corrosion coating, decreased adhesion, and reduced mechanical properties caused by the hydrophobic layer being too thick. The thickness of the transition layer is between 40-60μm, which can ensure that its water absorption is fully exerted and avoid the problems of increased cost of the anti-corrosion coating, increased aging rate, and decreased adhesion caused by the transition layer being too thick.
[0047] Exemplarily, the thickness of the hydrophobic layer is 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, etc., and the thickness of the transition layer is 12 μm, 45 μm, 47 μm, 50 μm, 52 μm, 55 μm, 57 μm, etc.
[0048] In a specific embodiment, the mass ratio of the magnetic water-absorbing resin to the epoxy resin is 1-3:10-30.
[0049] In one embodiment, the transition layer is prepared by a method comprising the following steps:
[0050] A first slurry including magnetic water-absorbing resin particles, epoxy resin, curing agent and solvent is applied to at least one surface of the substrate, and a magnet that repels the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles toward the substrate. After the first slurry coating is dry, a magnet that attracts the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles away from the substrate. After heating and curing, the transition layer is obtained.
[0051] Among them, the above-mentioned magnetic water-absorbing resin particles only refer to granular magnetic water-absorbing resin. As for the size of the particles, the present invention does not make any special limitation, and it can be micron-level or nano-level. In some embodiments, the average particle size of the magnetic water-absorbing resin particles is 40-100μm; further, the average particle size of the magnetic water-absorbing resin particles is any value of 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, etc.
[0052] The above preparation method mainly uses the principle of magnetic repulsion or attraction to adjust the relative position of the magnetic water-absorbing resin particles in the coating. It does not require multiple spraying, the preparation process is simple, and the problem of poor bonding between different coatings can be avoided. In detail, when the slurry is not solidified, the magnetic water-absorbing resin particles move toward the direction of the substrate. After the first slurry coating is dry, the first epoxy resin layer can be formed by controlling the thickness of the surface drying (surface drying). Then, the magnetic water-absorbing resin particles are moved away from the substrate, and the magnetism of the magnet or the residence time of the magnet is controlled, thereby controlling the moving distance and moving speed of the magnetic water-absorbing resin particles, thereby regulating the thickness of the transition layer. At the same time, the formation of the second epoxy resin layer can also be controlled, and finally heated and cured.
[0053] The above preparation method can be carried out by drying the first slurry coating under heating or room temperature. The temperature of the above heating and curing is not particularly limited by the present invention. In order to melt the above magnetic absorbent resin particles into a liquid state to improve the adhesion of the anti-corrosion coating, in some embodiments, the temperature of the above heating and curing is 120-200°C.
[0054] The present invention does not specifically limit the coating method of the first slurry. In order to make the coating more uniform, spraying is preferred.
[0055] In a second aspect, the present invention provides a method for preparing the anti-corrosion coating according to the first aspect, comprising the following steps:
[0056] 1) spraying a first slurry including magnetic water-absorbing resin particles, epoxy resin, curing agent and solvent on at least one surface of the substrate, suspending a magnet that repels the magnetic water-absorbing resin particles on the upper surface of the substrate, so that the magnetic water-absorbing resin particles move toward the substrate, and forming the first epoxy resin layer after the first slurry is dried, and then suspending a magnet that attracts the nanoparticles of the magnetic water-absorbing resin on the upper surface of the substrate, so that the magnetic water-absorbing resin particles move away from the substrate, and after curing, obtaining a second epoxy resin layer, a transition layer and a first epoxy resin layer stacked in sequence on the surface of the substrate;
[0057] 2) spraying a second slurry containing hydrophobic nano-SiO2 on the surface of the first epoxy resin layer, and obtaining the anti-corrosion coating after drying.
[0058] It can be understood that the above-mentioned magnetic water-absorbing resin microparticles only refer to granular magnetic water-absorbing resin. As for the size of the particles, the present invention does not specifically limit it, and it can be micron-sized or nano-sized. In some embodiments, the average particle size of the magnetic water-absorbing resin microparticles is 40-100μm.
[0059] The above preparation method mainly uses the principle of magnetic repulsion or attraction to adjust the relative position of the magnetic water-absorbing resin particles in the coating, and there is no problem of bonding force and stress between coatings; first, when the slurry is not solidified, the magnetic water-absorbing resin particles move toward the direction of the substrate, and after the first slurry coating is surface-dried, the first epoxy resin layer can be formed by controlling the thickness of the surface drying (surface drying), and then the magnetic water-absorbing resin particles are moved away from the substrate, and the magnetism of the magnet or the residence time of the magnet is controlled, thereby controlling the moving distance and moving speed of the magnetic water-absorbing resin particles, thereby regulating the thickness of the transition layer. At the same time, the formation of the second epoxy resin layer can also be controlled, and finally heated and cured.
[0060] The present invention does not specifically limit the coating method of the first slurry. In order to make the coating more uniform, spraying is preferred.
[0061] In some embodiments, in step 1), the solvent is deionized water; the curing agent is ethylenediamine, diethylenetriamine, diaminodiphenylmethane (DDM), diaminodiphenylethane, 2-methylimidazole, 2-ethyl-4-methylimidazole, etc.
[0062] In one specific embodiment, the magnetic water-absorbing resin microparticles are prepared by a method comprising the following steps:
[0063] Polyacetamide, ferrous chloride tetrahydrate, ammonia water, acrylic acid, initiator, crosslinking agent, dispersant and solvent are mixed, and after polymerization reaction, the mixture is dried and crushed to obtain microparticles of the magnetic water-absorbing resin.
[0064] In some embodiments, polyacetamide can be specifically selected from polyvinylpyrrolidone; the initiator can be selected from: potassium persulfate, polyglycerol monostearate; the cross-linking agent can be selected from: NN methylenebisacrylamide, ethylene glycol glycidyl ether, polyols, the dispersant can be selected from Span 80, Span 85; the solvent can be selected from: ethanol, deionized water.
[0065] In some embodiments, the mass ratio of the magnetic water-absorbing resin particles, the epoxy resin, the curing agent, and the solvent is 1:5:1:3.
[0066] In some embodiments, the drying in step 2) is natural air drying.
[0067] In a third aspect, the present invention provides a battery pack comprising the anti-corrosion coating described in the first aspect.
[0068] The anti-corrosion coating of the present invention is suitable for the anti-corrosion of various metal parts of battery packs, such as steel trays, bottom guard plates, sealing covers, etc.
[0069] It can be understood that the above battery pack also includes battery cells configured in series or in parallel, wherein the battery cells include positive and negative electrode sheets, a separator and an electrolyte; the positive electrode sheet includes a positive electrode active material, a conductive agent and a binder; the negative electrode sheet includes a negative electrode active material, a conductive agent and a binder
[0070] Exemplarily, the positive electrode active material can be selected from the positive electrode active materials commonly used in the art, for example, one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, and lithium iron phosphate; the negative electrode active material can be selected from the negative electrode active materials commonly used in the art, for example, one or more of graphite, silicon-doped graphite, and lithium titanate; the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate
[0071] The present invention has no particular limitation on the above-mentioned separator, and any known porous structure separator with electrochemical stability and chemical stability can be selected, for example, it can be at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The separator can be single-layer or multi-layer.
[0072] The electrolyte includes an organic solvent and an electrolyte salt. The organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and any organic solvent known in the art for battery electrolyte can be used.
[0073] For example, the organic solvent may be at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). In a specific embodiment, two or more of the above organic solvents may be selected.
[0074] The electrolyte salt is used as a source of ions, and an electrolyte salt for battery electrolyte known in the art can be used. Exemplarily, the electrolyte salt can be at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium nitrate (LiNO3), and lithium fluoride (LiF).
[0075] In a fourth aspect, the present invention provides an electrical device comprising the battery pack described in the second aspect.
[0076] It should be noted that the above-mentioned electronic equipment can be any conventional equipment that requires electricity, for example, including but not limited to computers, electric cars, air conditioners, refrigerators, washing machines, microwave ovens, printers, fax machines, etc.
[0077] The technical scheme of the present invention is further illustrated below in conjunction with specific examples. All parts, percentages and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0078] The curing agent models involved in the following tests are: JHY-901;
[0079] CAS number of epoxy resin: 61788-97-4.
[0080] Example 1
[0081] This example provides an anti-corrosion coating, combined with Figure 1 The anti-corrosion coating is arranged on the surface of the substrate 1, and the anti-corrosion coating includes: a second epoxy resin layer 2, a transition layer 3, a first epoxy resin layer 4, and a hydrophobic layer 5 are stacked in sequence from away from the substrate to the adjacent substrate; the transition layer includes: a magnetic water-absorbing resin and an epoxy resin; the magnetic water-absorbing resin includes polyacrylic acid and Fe3O4 (10-50nm); the hydrophobic layer is a hydrophobic nano-SiO2 coating; the substrate is an aluminum alloy (size 100mm×100mm×10mnm); the contact angle of the hydrophobic layer is greater than 90°.
[0082] The thickness of the first epoxy resin layer is 34 μm, and the thickness of the second epoxy resin layer is 72 μm; the thickness of the hydrophobic layer is 35 μm, and the thickness of the transition layer is 48 μm; the mass ratio of the magnetic water-absorbing resin to the epoxy resin is 1:30.
[0083] The preparation method thereof comprises the following steps:
[0084] 1) 0.125 g polyvinyl pyrrolidone, 2.601 g ferrous chloride tetrahydrate, 50 g ammonia water, 12.5 g acrylic acid (neutralization degree 80%), 0.05 g redox initiator potassium persulfate, 0.015 g crosslinking agent NN methylene bisacrylamide and deionized water are mixed, stirred at 40-90° C. to cause polymerization reaction; after stirring for 10 hours, the mixture is placed in an oven at 110° C. to dry; after drying, the magnetic water-absorbing resin is crushed into particles with a particle size of 40-100 μm for standby use;
[0085] 2) Mixing magnetic water-absorbing resin microparticles, epoxy resin, curing agent and ethanol in a mass ratio of 1:5:1:3 to obtain a first slurry, spraying the first slurry on the surface of the substrate, suspending a magnet that repels the magnetic water-absorbing resin microparticles on the upper surface of the substrate, so that the magnetic water-absorbing resin microparticles move toward the substrate, drying the first slurry coating at 50-80° C. to dry the surface of the first slurry coating to form the first epoxy resin layer, then suspending a magnet that attracts the nanoparticles of the magnetic water-absorbing resin on the upper surface of the substrate, so that the magnetic water-absorbing resin microparticles move away from the substrate, and curing at 180° C. to obtain a second epoxy resin layer, a transition layer, and a first epoxy resin layer stacked in sequence on the surface of the substrate;
[0086] 3) Spraying a second slurry containing hydrophobic nano-SiO2 on the surface of the first epoxy resin layer (in the second slurry, the hydrophobic nano-SiO2 is nano-SiO2 with 70wt% fluorosilane groups modified on the surface, with an average particle size of 200nm, and the solvent is a hydroxyl acrylic resin with a viscosity of 1000-3000mPa.s), and obtaining an anti-corrosion coating after drying.
[0087] Example 2-3
[0088] The anti-corrosion coating provided is substantially the same as that in Example 1, except that the parameters shown in Table 1 are changed.
[0089] Comparative Example 1
[0090] The anti-corrosion coating body provided is substantially the same as that in Example 1, except that the second epoxy resin layer 2 and the first epoxy resin layer 4 are not included.
[0091] Comparative Example 2
[0092] The anti-corrosion coating body provided is basically the same as that in Example 1, except that it only includes an epoxy resin layer and a hydrophobic layer, as shown in Table 1 for details.
[0093] The preparation method thereof comprises the following steps:
[0094] 1) epoxy resin, curing agent and ethanol are mixed in a mass ratio of 5:1:3 to obtain a first slurry, the first slurry is sprayed on the surface of the substrate, and after curing at 180° C., an epoxy resin layer laminated on the surface of the substrate is obtained;
[0095] 2) Spray the second slurry containing hydrophobic nano-SiO2 as in Example 1 on the surface of the epoxy resin layer, and obtain an anti-corrosion coating after drying.
[0096] Test Case
[0097] The ink permeability of the anti-corrosion coatings of the above-mentioned embodiments and comparative examples was tested, and the results are recorded in Table 1.
[0098] Among them, the test method of ink permeability is: testing according to (GB / T 1733 Determination of water resistance of paint film).
[0099] Table 1:
[0100]
[0101] It can be seen from Table 1 that compared with the comparative example, the ink permeability of the anti-corrosion coating of the embodiment is lower. By comparing the embodiments, it can be seen that the increase in the mass ratio of the magnetic absorbent resin particles will affect the thickness of the transition layer, and then affect the thickness ratio of the first epoxy resin layer and the second epoxy resin layer, and finally affect the permeability of the coating.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An anti-corrosion coating, the anti-corrosion coating is arranged on the surface of a substrate, characterized in that: The anti-corrosion coating comprises, from the surface adjacent to the substrate to the surface away from the substrate, a second epoxy resin layer, a transition layer, a first epoxy resin layer and a hydrophobic layer stacked in sequence; the transition layer comprises a magnetic water-absorbing resin and an epoxy resin.
2. The anti-corrosion coating according to claim 1, characterized in that: The magnetic water-absorbing resin comprises a water-absorbing high molecular polymer and Fe3O4; and / or the contact angle of the hydrophobic layer is greater than 90°.
3. The anti-corrosion coating according to claim 2, characterized in that: The water-absorbing high molecular polymer includes at least one of polyacrylic acid, polyacrylic acid salt, polyacrylamide, and carboxymethyl cellulose; and / or the hydrophobic layer is a hydrophobic nano-SiO2 coating.
4. The anti-corrosion coating according to claim 2 or 3, characterized in that: The particle size of the Fe3O4 is 10-50nm.
5. The anti-corrosion coating according to claim 4, characterized in that: The thickness of the first epoxy resin layer is 20-50 μm; and / or the thickness of the second epoxy resin layer is 70-100 μm.
6. The anti-corrosion coating according to any one of claims 1 to 5, characterized in that: The thickness of the hydrophobic layer is 20-50 μm; and / or the thickness of the transition layer is 40-60 μm.
7. The anti-corrosion coating according to any one of claims 1 to 5, characterized in that: The mass ratio of the magnetic water-absorbing resin to the epoxy resin is 1-3:10-30.
8. The anti-corrosion coating according to any one of claims 1 to 7, characterized in that: The transition layer is prepared by a method comprising the following steps: A first slurry including magnetic water-absorbing resin particles, epoxy resin, curing agent and solvent is applied to at least one surface of the substrate, and a magnet that repels the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles toward the substrate. After the coating is dry, a magnet that attracts the magnetic water-absorbing resin particles is suspended on the upper surface of the substrate to move the magnetic water-absorbing resin particles away from the substrate. After heating and curing, the transition layer is obtained.
9. A method for preparing an anti-corrosion coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) coating a first slurry including magnetic water-absorbing resin particles, epoxy resin, curing agent and solvent on at least one surface of the substrate, suspending a magnet that repels the magnetic water-absorbing resin particles on the upper surface of the substrate to move the magnetic water-absorbing resin particles toward the substrate, and forming the first epoxy resin layer after the coating is dried, and then suspending a magnet that attracts the magnetic water-absorbing resin nanoparticles on the upper surface of the substrate to move the magnetic water-absorbing resin particles away from the substrate, and after curing, obtaining a second epoxy resin layer, a transition layer and a first epoxy resin layer stacked in sequence on the surface of the substrate; 2) spraying a second slurry containing hydrophobic nano-SiO2 on the surface of the first epoxy resin layer, and obtaining the anti-corrosion coating after drying.
10. The preparation method according to claim 9, characterized in that: The magnetic water-absorbing resin microparticles are prepared by a method comprising the following steps: Polyacetamide, ferrous chloride tetrahydrate, ammonia water, acrylic acid, initiator, crosslinking agent, dispersant and solvent are mixed, and after polymerization reaction, the mixture is dried and crushed to obtain microparticles of the magnetic water-absorbing resin.
11. A battery pack, characterized in that: The invention comprises the anti-corrosion coating according to any one of claims 1 to 8.
12. An electrical equipment, characterized in that: A battery pack comprising the battery pack of claim 11.
Citation Information
Cited By
An insulating anticorrosive sintering-resistant integrated coating material, a preparation method and application thereof
CN122832587A